2023
DOI: 10.4018/978-1-6684-8198-1.ch003
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Success

Abstract: Student success continues to be an important topic in the higher education literature as students often struggle with university transition. Success is typically measured through the lens of retention or grades. However, retention in particular may not always be the best indicator, especially in universities with minimal drop-out rates. The present study was conducted in a Hong Kong government-funded university and seeks to understand first-year students' perspectives on what constitutes success. Three focus g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…This variable is considered an important indicator of academic success and permanence of students (Pérez et al, 2020). For the achievement of an adequate integration into Cobo-Rendón et al 10.3389/feduc.2023.1303765 university life, empirical evidence has shown that contributing to the adaptation of young student's elements such as emotions, wellbeing, and perception of support is essential for their development, and this is because during the transition processes students experience emotions such as anxiety, hopelessness, worry, and stress (Chan and Rose, 2023;Hako et al, 2023). Adaptation to university life is critical to permanence and depends, from the student's point of view, on the social experiences and resources that the student uses at the university (Van Rooij et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This variable is considered an important indicator of academic success and permanence of students (Pérez et al, 2020). For the achievement of an adequate integration into Cobo-Rendón et al 10.3389/feduc.2023.1303765 university life, empirical evidence has shown that contributing to the adaptation of young student's elements such as emotions, wellbeing, and perception of support is essential for their development, and this is because during the transition processes students experience emotions such as anxiety, hopelessness, worry, and stress (Chan and Rose, 2023;Hako et al, 2023). Adaptation to university life is critical to permanence and depends, from the student's point of view, on the social experiences and resources that the student uses at the university (Van Rooij et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A successful transition of students to college life is an essential element to consider when discussing educational quality, as this transition is associated with academic success, retention, social development, and personal growth that can shape students' future success and wellbeing (Chan and Rose, 2023).…”
Section: Academic Emotions In University Studentsmentioning
confidence: 99%
“…This variable is considered an important indicator of academic success and permanence of students (Pérez et al, 2020). For the achievement of an adequate integration into university life, empirical evidence has shown that contributing to the adaptation of young student's elements such as emotions, wellbeing, and perception of support is essential for their development, and this is because during the transition processes students experience emotions such as anxiety, hopelessness, worry, and stress (Chan and Rose, 2023;Hako et al, 2023). Adaptation to university life is critical to permanence and depends, from the student's point of view, on the social experiences and resources that the student uses at the university (Van Rooij et al, 2018).…”
Section: Introductionmentioning
confidence: 99%